From DNA barcoding to personalized nutrition: the evolution of food traceability. (August 2019) - Galimberti, Andrea; Casiraghi, Maurizio; Bruni, Ilaria; Guzzetti, Lorenzo; Cortis, Pierluigi; Berterame, Nadia Maria; Labra, Massimo
Highlights: Safe and healthy nutrition requires authentication of food products. Raw ingredients, processed, and mixed food products could lack diagnostic traits to enable identification. DNA barcoding and DNA metabarcoding emerged as reliable tools for food authentication. DNA-based tools are also reliable in characterizing the food microbiome and food safety. DNA-based tools will enter into the customization of healthy diets. Abstract : A genuine nutritional product is pivotal for getting proper health benefits and preventing pathologies. However, with the increase in global trading of raw and processed food products, reliable authentication is essential for correct labelling to ensure consumer safety. The use of DNA-based tools has become a prospective solution in the near future to solve this problem. Currently, technologies exploiting DNA polymorphism between species are able to characterize the food composition of pure (DNA barcoding) or multi-species (DNA metabarcoding) food items, and the application of this technology has started entering into food regulations. Here, we provide a brief overview of the history, success, and forthcoming applications of such approaches, while also considering the influence of food on human microbiota and the emerging trends toward the adoption of a 'personalized nutrition'.